Religion, Mysticism, and Transcultural Entanglements in Modern South Asia - Mukherjee, Soumen. author. aut Link
XVII, 201 p. 2 illus.
Keywords: “An insightful study of the spiritual quest undertaken by an impressive array of South Asian intellectuals who reappraised the very meaning of religion. Far from being a mode of inward-looking cultural defense, Soumen Mukherjee convincingly interprets mysticism and spirituality as a cosmopolitan pursuit by creative thinkers delving into devotional traditions of India’s past while responding to global challenges of the early twentieth century.” — Sugata Bose, Gardiner Professor of Oceanic History and Affairs, Harvard University “A detailed and erudite study of the way in which mysticism and spirituality came to dominate Indian forms of selfhood and self-making from the first half of the twentieth century. Part of a global debate spanning Asia, Europe, and America, interest in the esoteric and metaphysical distinguished Indian thinkers from their peers in other countries while nevertheless joining them in conversation to make for a truly global debate on the meaning and freedom of the self.” — Faisal Devji, Professor of Indian History, University of Oxford and Fellow, St Antony’s College “In India, as in many other Asian contexts, claims of modernity have sat uneasily with histories and traditions of mysticism and spirituality… This outstanding book helps us break out of such unproductive dichotomies by focusing on religious and cultural discussions in India in the early twentieth century… Yet, this riveting book is neither conventionally parochial nor fashionably global— it hypostasizes ‘spiritual cosmopolitans’ situating thinkers within contexts of transregional religious movements and networks.” —Samita Sen, Vere Harmsworth Professor of Imperial and Naval History, University of Cambridge and Fellow, Trinity College This book explores the location of spirituality and mysticism in modern Indian religious and intellectual life. It examines select personalities and their ideas since the early twentieth century, their role in the interwoven spheres of socio-religious and political thought, and in burgeoning spiritual imaginaries, often at the intersection of academic and public discourse. As part of a global ecumene connected by affective bonds, these spiritual cosmopolitans often defied binary frameworks (East/ West; imperial core/ periphery; colonizer/ colonized), and in the upshot reappraised and recast the very concept of religion in response to overarching ‘this-worldly’ exigencies. Soumen Mukherjee teaches History at Presidency University in Kolkata. He is the author of Ismailism and Islam in Modern South Asia: Community and Identity in the Age of Religious Internationals (2017). .